Perspektywy rozwoju sektora transportu w Polsce - Wasiak, Andrzej (Prospects for the Development of Transport Sector in Poland, 2006)
This article describes the issues associated with the challenges and prospects of development of transport, which is one of the most complex sectors of Polish economy and infrastructure in the aspects of national and local government policy. Means of transport are a pre-requisite for effective functioning of the economy. It is a major factor in social and economic development, which allows indispensable mobility. Techniques, technology, organisation and management systems associated with transportation are subject to continuous development and go through various improvement phases. Modern transport policy is aimed at creating optimum environment for effective, safe, economically viable and environment friendly transport of loads and goods. Transport policy is concerned with building a transport system that will harmonise with the environment at the times of scarce energy, material, capital and other resources. Such policy will result in the development of a transport system that is free from inconvenience and problems. This is invariably an organisational but most of all financial problem.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 107-121